Komunikasi Matematis pada Tugas dalam Buku Teks Matematika SMP Kelas VIII Kurikulum Merdeka Konten Geometri - Merin Vandira Gatsmir; Evangelista Lus Windiyana Palupi (MATHEdunesa, 2023)
Mathematical communication is the process of expressing mathematical ideas through drawings, symbols, and other to clarify mathematical problems. One of the efforts to enhance students' mathematical communication is through tasks in the mathematics textbook. The purpose of this research is to analyze and describe mathematical communication in tasks within the grade VIII mathematics textbook of the Merdeka Curriculum, specifically focusing on geometry content. This research is a qualitative content analysis. The object of this research is the tasks related to geometry content in the grade VIII mathematics textbook published by the Ministry of Education, Culture, Research, and Technology and Erlangga. The tasks are classified into activities or exercises using a task classification sheet, and the occurrence of mathematical communication indicators in each task is collected using a classification sheet. The results showed that the tasks in the grade VIII mathematics textbook published by Ministry of Education, Culture, Research, and Technology and Erlangga contains all indicators of mathematical communication. These indicators include communicating problem-solving strategies (66,7% & 63,9%), communicating ideas and problem solutions (100% for both), communicating students' mathematical thinking coherently (47,9% & 40,3%), communicating students' mathematical thinking clearly (17,7% & 36,1%), analyzing other people's mathematical thinking and strategies (6,3% & 2,8%), evaluating other people's mathematical thinking and strategies (2,1% & 1,4%), using mathematical symbols and terms to express mathematical ideas (100% & 97,2%), using tables and drawings to express mathematical ideas (12,5% for both), and using students’ own language/sentences to express mathematical solutions (61,5% & 59,7%).